MANAJEMEN DAKWAH PENYULUH AGAMA ISLAM KECAMATAN DARMA KABUPATEN KUNINGAN DALAM MENGENTASKAN BACA TULIS AL-QURAN - Nurislamiah, Mia (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2021)
The purpose of this study is to determine the planning, organizing, actuating and controlling of Islamic religious educators in alleviating reading and writing the Al-Quran in, Darma District, Kuningan Regency. This study uses a constructivist approach and paradigm by using qualitative research methods. Based on this approach, the next analysis knife that the author uses is a case study technique and is analyzed using triangulation of data sources. The results of this study indicate that (1) the planning (planning) of Islamic religious instructors implementing one of the programs to eradicate reading and writing of the Al-Quran can run according to the expectations of the leadership, including holding a meeting to prepare all the things needed, determine the implementers, and determine all matters. facilities in the implementation of the process of eradicating the reading and writing of the Al-Quran. (2) Organizing the tasks assigned to Islamic religious instructors are tasks that are in accordance with their expertise and the work program provided by Islamic religious instructors is to provide the best facilities in alleviating Al-Quran reading and writing. This is done in order to facilitate the division of tasks and the preparation of work plans for Islamic religious instructors. Of course, various opportunities and obstacles were traversed with full struggle and patience so that da'wah could run well. (3) One of the management movements (actuating) carried out by the leadership is by providing motivation and enthusiasm to their subordinates so that Islamic religious instructors can work well and carry out their respective duties in order to achieve the program to eradicate reading and writing Al-Quran. (4) Controlling is carried out by the leadership, namely by observing all activities and tasks of Islamic religious instructors so that the achievement of the program to eradicate reading and writing Al-Quran can be carried out properly and as expected.